Let's solve the given equation step by step starting from the beginning:
-
Original Equation:
\[ 3 + 4 \left| \frac{x}{2} \right| + 3 = 11 \] -
Simplify:
Combine like terms: \[ 4 \left| \frac{x}{2} \right| + 6 = 11 \] -
Isolate the Absolute Value:
Subtract 6 from both sides: \[ 4 \left| \frac{x}{2} \right| = 5 \] -
Divide by 4:
\[ \left| \frac{x}{2} \right| = \frac{5}{4} \] -
Remove the Absolute Value:
This gives us two equations: \[ \frac{x}{2} = \frac{5}{4} \quad \text{and} \quad \frac{x}{2} = -\frac{5}{4} \] -
Solve for x in Each Case:
- First Case: \[ \frac{x}{2} = \frac{5}{4} \implies x = \frac{5}{4} \times 2 = \frac{10}{4} = \frac{5}{2} \]
- Second Case: \[ \frac{x}{2} = -\frac{5}{4} \implies x = -\frac{5}{4} \times 2 = -\frac{10}{4} = -\frac{5}{2} \]
Thus, the solutions to the given absolute value equation are:
\[ x = \frac{5}{2} \] and \[ x = -\frac{5}{2} \]
Therefore, the other solution to the given absolute value equation is:
\[ \boxed{-\frac{5}{2}} \]